Relaparotomy after caesarean section - Shrestha, Reena; Karki, Laxmi RC; Shrestha, Sarada Duwal; Malla, Anagha Pradhan; Pradhan, Binita; Singh, Alka; Shah, WuFei; Gurung, Padma; Lama, Sushma (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Relaparotomy after caesarean section is rare and literature are scanty. The decision requires a good clinical judgment to save mother’s life. Our objective was to analyse the outcome of relaparotomy after caesarean section at Patan Hospital. Methods: This was a cross sectional study done at the department of obstetrics and gynaecology, Patan Hospital, Lalitpur, Nepal. Charts of the caesarean section from January 2010 to December 2014 were reviewed to analyze the cases of relaparotomy for incidence, indication, management and outcome. Descriptive analysis was done using SPSS. Results: During 5 years, there were 17,538 caesarean deliveries, 39.15% of total 44,788 deliveries. Relaparotomy was done in 15 cases, 0.085% of 17,538 caesarean. Mean age was 26.6±4.7 years, 14 (93.3%) were between 25-35 years, 12 (80%) were primigravida. Indications for relaparotomy were pyoperitoneum (40%), hemoperitoneum (33.3%) and rectus sheath hematoma (26.7%). Out of 15 relaparotomies, 14 were conservative surgery and one required hysterectomy. There was no maternal mortality. Conclusions: Relaparotomy rate in our study was eight in 10,000. Those requiring relaparotomy had fetal distress as indication for first caesarean. Journal of Patan Academy of Health Sciences. 28 2016 Dec;3(2):28-31